2001
DOI: 10.1093/emboj/20.21.5840
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the interaction of the free SH2 domain EAT-2 with SLAM receptors in hematopoietic cells

Abstract: The T and natural killer (NK) cell-specific gene SAP (SH2D1A) encodes a 'free SH2 domain' that binds a specific tyrosine motif in the cytoplasmic tail of SLAM (CD150) and related cell surface proteins. Mutations in SH2D1A cause the X-linked lymphoproliferative disease, a primary immunodeficiency. Here we report that a second gene encoding a free SH2 domain, EAT-2, is expressed in macrophages and B lympho cytes. The EAT-2 structure in complex with a phosphotyrosine peptide containing a sequence motif with Tyr28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 52 publications
3
129
3
1
Order By: Relevance
“…EAT-2A is mainly expressed in natural killer cells (but also in B cells, mast cells and macrophages) and has been shown to inhibit natural killer-cell function through tyrosine phosphorylation. 31,32 In fact, Sh2d1b-deficient mice (EAT-2A À/À ) exhibited enhanced natural killer-cell cytotoxicity as well as increased IFN-g secretion upon stimulation with anti-CD16, NKG2D, Ly49D and CD224. 32 Notably, Sh2d1b is highly polymorphic with at least 76 known single nucleotide polymorphisms in various mouse strains, increasing the likelihood that polymorphisms between B6 and NZB mice exist.…”
Section: Discussionmentioning
confidence: 99%
“…EAT-2A is mainly expressed in natural killer cells (but also in B cells, mast cells and macrophages) and has been shown to inhibit natural killer-cell function through tyrosine phosphorylation. 31,32 In fact, Sh2d1b-deficient mice (EAT-2A À/À ) exhibited enhanced natural killer-cell cytotoxicity as well as increased IFN-g secretion upon stimulation with anti-CD16, NKG2D, Ly49D and CD224. 32 Notably, Sh2d1b is highly polymorphic with at least 76 known single nucleotide polymorphisms in various mouse strains, increasing the likelihood that polymorphisms between B6 and NZB mice exist.…”
Section: Discussionmentioning
confidence: 99%
“…To focus on the most relevant target residues of the SAP molecule, we took advantage of the fact that EAT-2 and SAP SH2 domains share a similar overall structure and 47% amino acid identity, and are expected to bind to the same set of SLAMF ITSMs (11). As shown in Fig.…”
Section: Sap Is Required For Optimal T-b Adhesion Soon After Ligand Rmentioning
confidence: 99%
“…Previous work showed that SLAM/SLAM interactions inhibit production of IL-12 and IL-6 by CD40L-activated DC (10). EAT-2 interacts with p-SLAM family receptors, such as CD84, CD150, LY9, and CD244, in immune cells and has been shown to be a negative regulator of cellular activation downstream of the SLAM receptor 2B4 in NK cells (11)(12)(13). Therefore, we questioned whether one of the mechanisms by which reduced EAT-2 leads to enhanced cytokine production was through impaired negative regulation of CD40 stimulation in DC.…”
Section: Resultsmentioning
confidence: 99%